Reference: A Grammatical Cohesion In Seloka Journal Introduction Published by Semarang State University - Samsudin Syam (Politeknik Negeri Padang, 2020)
Good writing is one that is cohesive especially in terms of reference. Cohesive is one of the essential textual components to create the organized and comprehensiveness of the texts. This study aims to investigate cohesion in six journal introduction sections written by post-graduate students at Semarang State University, West Java, Indonesia. This study used discourse analysis as an approach to analyzing grammatical cohesive devices. six journal introduction sections were chosen based on purposive sampling. The journal introduction sections were analyzed using Halliday and Matthiessen (2014) theory that contributing to the cohesion of the text, namely cohesive devices. The results of this study showed that post-graduate students at Semarang State University tend to use demonstrative references more frequently than the other grammatical cohesive devices. From 393 occurrences of grammatical cohesive devices presented in the six journal introduction sections, 322 of them were in the form of demonstrative reference. Through this article, the writer wants to help un English post-graduate students to have a better understanding of making introduction sections in their journal article.